Gender across languages. the linguistic representation of women and men - Hellinger, Marlis; Bussmann, Hadumod (Impact, studies in language and society, 2003)
This is the third of a three-volume comprehensive reference work on "Gender across Languages", which provides systematic descriptions of various categories of gender (grammatical, lexical, referential, social) in 30 languages of diverse genetic, typological and socio-cultural backgrounds. Among the issues discussed for each language are the following: What are the structural properties of the language that have an impact on the relations between language and gender? What are the consequences for areas such as agreement, pronominalisation and word-formation? How is specification of and abstract